2016
DOI: 10.1111/gtc.12449
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of Hmo1 mediated by box A is essential for DNA binding in vitro and in vivo

Abstract: Hmo1, a member of HMGB family proteins in Saccharomyces cerevisiae, binds to and regulates the transcription of genes encoding ribosomal RNA and ribosomal proteins. The functional motifs of Hmo1 include two HMG-like motifs, box A and box B, and a C-terminal tail. To elucidate the molecular roles of the HMG-like boxes in DNA binding in vivo, we analyzed the DNA-binding activity of various Hmo1 mutants using ChIP or reporter assays that enabled us to conveniently detect Hmo1 binding to the promoter of RPS5, a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…As a reciprocal experiment, we examined the requirement of Fpr1 for Hmo1 binding to RPG promoters, which revealed that in the fpr1 Δ strain, Hmo1 binding to the promoters of RPS5 , RPL25 and RPS30B was not or only slightly affected ( Fig 2C , upper panels). The results of a previous study conducted using a yeast two-hybrid system suggested that Fpr1 could promote Hmo1 dimerization [ 26 ], which is required for DNA binding [ 38 ]. Although Fpr1 might affect Hmo1 binding to DNA through its interaction with Hmo1, such an effect, if present, might be limited to certain loci (or to nonspecific loci throughout the genome).…”
Section: Resultsmentioning
confidence: 99%
“…As a reciprocal experiment, we examined the requirement of Fpr1 for Hmo1 binding to RPG promoters, which revealed that in the fpr1 Δ strain, Hmo1 binding to the promoters of RPS5 , RPL25 and RPS30B was not or only slightly affected ( Fig 2C , upper panels). The results of a previous study conducted using a yeast two-hybrid system suggested that Fpr1 could promote Hmo1 dimerization [ 26 ], which is required for DNA binding [ 38 ]. Although Fpr1 might affect Hmo1 binding to DNA through its interaction with Hmo1, such an effect, if present, might be limited to certain loci (or to nonspecific loci throughout the genome).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, we hypothesized that Hmo1 might bind to the nucleosomes and link adjacent nucleosomes via oligomerization. This hypothesis is supported by the fact that Hmo1 can form higher-order oligomers ( 82 , 83 ) and shows gel-like phase separation properties when mixed with dsDNA ( Fig. 5 ).…”
Section: Discussionmentioning
confidence: 75%